2008
DOI: 10.1086/524009
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Spectral Modeling of a Three‐dimensional Pulsating Reverse Detonation Model: Too Much Nickel

Abstract: We calculate detailed non-LTE synthetic spectra of a pulsating reverse detonation (PRD) model, a novel explosion mechanism for Type Ia supernovae. While the hydro models are calculated in three dimensions, the spectra use an angle-averaged hydro model and thus some of the three-dimensional (3D) details are lost, but the overall average should be a good representation of the average observed spectra. We study the model at three epochs: maximum light, 7 days prior to maximum light, and 5 days after maximum light… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The composition profile in the GCD model is therefore significantly different from that in the pulsational reverse detonation (PRD) model described by Bravo & García-Senz (2006) and discussed in Baron et al (2008). The total mass of Fe-peak material in the outer layers is significantly smaller in the GCD model, residing within a thin surface layer overlying a region rich in IMEs.…”
Section: The Velocity Distribution Of the Yieldmentioning
confidence: 72%
“…The composition profile in the GCD model is therefore significantly different from that in the pulsational reverse detonation (PRD) model described by Bravo & García-Senz (2006) and discussed in Baron et al (2008). The total mass of Fe-peak material in the outer layers is significantly smaller in the GCD model, residing within a thin surface layer overlying a region rich in IMEs.…”
Section: The Velocity Distribution Of the Yieldmentioning
confidence: 72%
“…At the same time, the observed characteristics of SN Ia light curves and spectra can be fairly matched by adopting radial and/or axial shifts in the distribution of 56 Ni, possibly due to a delayed-and/or pulsational-detonation-like explosion mechanism (see Khokhlov 1991b;Hoflich et al 1995;Baron et al 2008Baron et al , 2012Bravo et al 2009;Maeda et al 2010b;Dessart et al 2013a) or a merger scenario (e.g., Dan et al 2013;Moll et al 2013). Central ignition densities are also expected to play a secondary role in the form of the WLR since they are dependent upon the accretion rate of H and/or He-rich material and cooling time Höflich et al 2010;Meng et al 2010;Krueger et al 2010;Sim et al 2013), in addition to the spin-down timescales for differentially rotating WDs (Hachisu et al 2012;Tornambé and Piersanti 2013).…”
Section: Light Curvesmentioning
confidence: 85%
“…To their advantage, these deflagrationto-detonation transition (DDT) and pulsating delayed-detonation (PDD) models are able to reproduce the observed characteristics of SN Ia, however not without the use of an artificially-set transition density between stages of burning (Khokhlov 1991b;Hoflich et al 1995;Lentz et al 2001aLentz et al , 2001bBaron et al 2008;Bravo et al 2009;Dessart et al 2013a). Subsequently, a bulk of the efforts within the modeling community has been the pursuit of conditions or mechanisms which cause the burning front to naturally transition from a sub-sonic deflagration to a super-sonic detonation, e.g., gravitationally confined detonations (Jordan et al 2009), prompt detonations of merging WDs, a.k.a.…”
Section: Modelsmentioning
confidence: 99%
“…Models GCD1 and TURB7 synthesize a large amount of 56 Ni and, due to their large kinetic energy and the presence of radioactive nuclei up to the surface of the ejecta, decline much faster than observations seem to indicate (the main parameter determining the width of the bolometric light curve is the photon diffusion time, t d , that is in turn affected by the kinetic energy: t d ∝ K −1/4 , Woosley et al 2007). Baron et al (2008) obtained detailed spectra of angle-averaged one-dimensional versions of several PRD models, from slightly before up to a few days after maximum light. They concluded that the synthetic spectra of the PRD models did not match the spectra of a few typical wellobserved SNIa.…”
Section: Light Curvesmentioning
confidence: 99%